Upstream disturbance effects on self-similarity in the wake of a DrivAer model - Rallapalli, Anurag; Proenca, Anderson R.; Garry, Kevin (Society of Automotive Engineers (SAE), 2023)
This study aims to provide an understanding of self-similarity in the turbulent wake generated by a Fastback DrivAer automotive model and assess the impact of upstream disturbances on the wake. The disturbances are generated using a circular cylinder placed five cylinder diameters upstream. Multiple ‘cylinder-model’ positions were tested by offsetting the lateral positioning of the cylinder with respect to the centreline of the model. Data was obtained at cross-planes in the wake going from 25% to 100% car length. Wind tunnel data has been obtained using a total pressure probe rake and a four-hole cobra probe. Data has also been obtained using RANS based simulations with k – ε realisable turbulence model. Mean axial-component velocity profiles were analysed with momentum thickness (θ) and vorticity thickness (δω) used as the scaling parameters. It was seen that self-similarity marginally exists in the wake depending on the upstream conditions and the scaling parameter. Overall, vorticity thickness was seen to be better. Downstream, the mean profiles show a simpler collapse compared to the near wake. Understanding how deficit decay takes effect in the wake is useful to improve the aerodynamic performance of an automobile/motor car/ground vehicle. Therefore, establishing the similarity parameters presented in the work is an early step towards an analytical description of a turbulent wake model.